Navigating Custody: The Impact of Religious Court Judges on Interfaith Family Dynamics - Mursyid, Salma; Bilalu, Naskur; Subeitan, Syahrul Mubarak (Al-Mujtahid: Journal of Islamic Family Law, 2024)
This study examines the critical role of Religious Court judges in deciding child custody in families with parents of different religions in Indonesia. Religious Court judges face unique challenges in balancing Islamic legal principles with children's best interests in a complex and diverse social context. This study aims to identify factors that affect judges' decisions, including legal foundations, moral considerations, and social impacts. Using a qualitative approach, data were obtained through in-depth interviews with judges, case analysis, and literature reviews. The study results show that judges consider not only formal law but also social values and the interests of children. Factors such as the child's psychological condition, emotional stability, and a healthy growth and development environment are the primary considerations in decision-making. In addition, the study found that the diversity of interpretations of Islamic law among judges influenced their final decisions. This study found that Religious Court judges consider not only formal law but also social values and the best interests of children in making decisions on child custody in families of different religions. In addition, the diversity of interpretations of Islamic law among judges also influences the final decision, with factors such as the child's psychological condition and emotional stability being the primary considerations.